A pesquisa sobre formação de professores e multiculturalismo no Brasil : tendências e desafios - Mariano, André Luiz Sena (Universidade Federal de São Carlos, 2009)
The present study advocates the thesis that the prevalence of conservative multicultural perspective and found in the studies selected, enable the construction of essentialized identities and the suffocation of the differences. This perspective is a major obstacle to the design - advanced here - training of teachers as intellectuals, with a mandate of heir, artist and critic, who understand the identities and differences as products and producers of history, culture, ideology, and also power relations. Therefore, structured the work around the question: what the studies produced and published in Brazil, when addressing the integration of multiculturalism in teacher education, reveal? This central issue unfolds in others: How does this integration occurs in the curriculum of teacher training? What (is) design (s) of multiculturalism is (are) present (s) in this work? How multicultural categories (social class, race / ethnicity, gender, etc.) have been included in the work selected? And to answer the questions above, have set the universe for the construction and analysis of data, journal articles - The International and The National - and the papers presented at major events in the area of education, namely: the Annual Meetings of the Association National Post-Graduate Studies and Research in Education (ANPEd) and the National Meetings of Curriculum and Teaching Practice (ENDIPE) between the years 2000 and 2006. Among the main trends in the 57 selected texts, stands within a multicultural conservative and a liberal left in the reality of teacher training. Through them, the teacher takes the difference of treatment as having a psychological or biological imprint, and thus one aspect of establishing hierarchies, inferiority those that differ from the ideal standard. The difference is always something missing to the individual or a diversion. The identity is treated essentialized and binary: the male as opposed to female, white as opposed to black. There are few studies that assume a hybrid identity. Moreover, the relationship between majority and minority is taken on a Manichean perspective, polarizing the oppressed group and the group oppressor. Finally, the teacher is still under the aegis of the technicality, allowing for a break between theory and practice and the preparation of teachers - both in the initial and ongoing - that works in favor of maintaining the status quo. Conclude that there is much to build toward a multicultural education, that gives rise to teacher training with a term of intellectual heir, interpreter and critic. Moreover, the teacher rights, multiculturalism needs to be taken as a discourse of hope and possibility.
Research on teacher education and multiculturalism in Brazil: trends and challenges
Keywords: Professores - formação; Multiculturalismo; Metodologia de ensino; Professor intelectual; Teacher education; Multiculturalism; Teacher intellectual; CIENCIAS HUMANAS::EDUCACAO